Orofacial Crohn's disease : an oral enigma - Fatahzadeh, Mahnaz (Array, 2009)
Summary: Crohn’s disease is a chronic, relapsing, inflammatory disorder which may involve any segment of the bowel from mouth to anus. The mucocutaneous manifestations of Crohn’s disease in the orofacial region are multiple, including oral Crohn’s disease, metastatic Crohn’s disease in sites noncontiguous with the bowel system, and reactive disorders such as pyoderma gangrenosum. Clinicians should be familiar with these extraintestinal manifestations and include this important and often serious disease in the evaluation of patients with selected orofacial disorders. The recognition of these manifestations may help prevent misdiagnosis and unnecessary treatment, and facilitates timely diagnosis, palliation and definitive therapy